Thibbun Nabawi dalam Pendidikan Islam : Relevansi Madu Sebagai Pengobatan Zaman Moderen - Halimah Tussakdiah; Sumayyah Abizar; Khairani Ulfa; Dwi Meutia Hasni (STIKes Ibnu Sina Ajibarang, 2025)
Thibbun nabawi is a method of treatment derived from the teachings of Prophet Muhammad (peace be upon him) that is not only based on medical science but also on the spiritual values of Islam. This treatment complements and perfects modern medical science, emphasizing the importance of balance between physical and spiritual health. One form of treatment in thibbun nabawi is the use of honey, which has been scientifically proven to have various health benefits. Honey functions as an antibacterial, anti-inflammatory, prebiotic, and as a source of natural nutrition that is safe for consumption by all ages, including pregnant women. In the context of modern medicine, honey shows great potential as a complementary therapy in addressing various diseases, such as diarrhea, acne vulgaris, and digestive disorders. Recent research also shows that honey consumption can reduce nausea and vomiting symptoms in pregnant women during the first trimester. Therefore, the integration of thibbun nabawi, particularly honey therapy, into the modern healthcare world should be further developed as a form of harmonization between medical science and Islamic values.